D2 receptor overexpression in the striatum leads to a deficit in inhibitory transmission and dopamine sensitivity in mouse prefrontal cortex - Li, Yan-Chun (National Academy of Sciences, 2011)
Two distinct defects are thought to be important for the pathophysiology of schizophrenia. One is an increase of D2 receptors (D2Rs) in the striatum and another is a decrease in the GABAergic function in the prefrontal cortex (PFC). Whether these two defects are functionally linked is not known. We previously reported that selective overexpression of D2Rs in the striatum of the mouse causes behavioral abnormality associated with PFC functions. Using patch-clamp recording, we find that overexpression of D2Rs in the striatum affects inhibitory transmission in the PFC and dopamine (DA) sensitivity. The overexpression of D2Rs in the striatum caused an increase in frequency of spontaneous excitatory postsynaptic currents (EPSCs) in layer V pyramidal neurons, whereas their neuronal excitability was unaffected. In contrast, both the frequency and amplitude of spontaneous inhibitory postsynaptic currents (sIPSCs) were significantly decreased in these mice, indicating a reduced inhibitory transmission. Furthermore, in D2R transgenic mice the dopaminergic modulation of evoked IPSCs was shifted, with reduced sensitivity. The change in dopamine sensitivity in the PFC of D2R transgenic mice appears specific for D2Rs because in D2R transgenic mice the effects of D2 agonist but not D1 agonist, on both evoked IPSCs and EPSCs, were reduced. Together, these results indicate that overexpression of D2Rs in the striatum leads to a functional deficit in the GABAergic system. These results provide a functional link between D2R overexpression and GABAergic inhibition in the PFC and suggest that the postulated deficit in GABAergic function in schizophrenia could be secondary to alterations in the striatal dopamine system.